2000
DOI: 10.1254/jjp.84.196
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SMP-300, a New Na+/H+ Exchange Inhibitor, on Myocardial Ischemia and Experimental Angina Models in Rats

Abstract: We evaluated the effects of SMP-300 (N-(aminoiminomethyl)-11-chloro-5,6,7,8-tetrahydro-8-oxo-4H-pyrrolo[3,2,1-kl][1]benzazocine-2-carboxamide monomethanesulfonate monohydrate), a newly synthesized compound, on Na+/H+ exchange activity in rat cardiomyocytes and on other ion transporters, channels and receptors. We also investigated the protective effects of SMP-300 in isolated ischemic rat hearts and rat isoproterenol- or vasopressin-induced experimental angina models. SMP-300 concentration-dependently inhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 32 publications
2
7
0
1
Order By: Relevance
“…The present study confi rmed previous reports that systemic administration of AVP in Donryu rats caused electrocardiographic S-wave depression, indicative of myocardial ischemia [10,14,20,22] . However, as expected, AVP also signifi cantly increased systemic blood pressure, which was not often investigated in other studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study confi rmed previous reports that systemic administration of AVP in Donryu rats caused electrocardiographic S-wave depression, indicative of myocardial ischemia [10,14,20,22] . However, as expected, AVP also signifi cantly increased systemic blood pressure, which was not often investigated in other studies.…”
Section: Discussionsupporting
confidence: 92%
“…Electrocardiogram (ECG) ST segment shift is commonly used as a non-invasive index of myocardial ischemia. Systemic administration of AVP can induce S-wave depression in Donryu rats, which has been used as an experimental model of myocardial ischemia [10,20,22] . However, the mechanism for AVP-induced S-wave depression in this model is unclear since AVP can cause both coronary vasoconstriction and systemic hypertension, thus affecting both myocardial oxygen supply and demand.…”
mentioning
confidence: 99%
“…Changes in ST-segment were used as an index of ischemic severity. According to the previous report (2), the fall of S-wave was regarded as the fall of ST. Maximal S-wave depression was observed 4 -5 min following AVP injection, consistent with previous reports (10,11). Both benidipine (3 and 10 m g / kg) and diltiazem (300 and 1000 mg/ kg) significantly inhibited the S-wave depression in a dose-dependent manner (Fig.…”
supporting
confidence: 91%
“…According to a previous report, 5) the fall of the Swave was regarded as the fall of ST. Maximal S-wave depression was observed about 4 min after AVP injection (data not shown), and is consistent with the results of previous reports. [7][8][9] Benidipine signiˆcant-ly inhibited the depression at 3 and 10 mg/kg in a dose-dependent manner (Fig. 2).…”
Section: Resultsmentioning
confidence: 88%
“…4) AVP-induced angina is a useful model for evaluating the e‹cacy of compounds in vasospastic angina. [5][6][7][8] Karasawa et al 5) reported that benidipine has beneˆ-cial eŠects in various experimental angina models, including the AVP-induced angina model. We have demonstrated recently that the antianginal e‹cacy of benidipine 10 mg/kg was similar to that of diltiazem 1000 mg/kg in the AVP-induced angina rat model, indicating that benidipine exerts potent antivasospastic anginal eŠects.…”
Section: Introductionmentioning
confidence: 99%